Screening for Chromosomal Abnormalities by First Trimester Combined Screening and Noninvasive Prenatal Testing - Kagan, K. O.; Hoopmann, M.; Hammer, R.; Stressig, R.; Kozlowski, P. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: To examine combined first trimester screening (FTS), noninvasive prenatal testing (NIPT) and a two-step policy that combines FTS and NIPT in screening for aneuploidy.Materials and Methods: Retrospective study involving 21 052 pregnancies where FTS was performed at the Praxis Praenatal.de in Duesseldorf, Germany. In each case, the sum risk of trisomy 21, 18 and 13 was computed. We assumed that NIPT detects 99 %, 98 %, 90 % and 99 % of cases with trisomy 21, 18, 13 and sex chromosomal abnormalities and that the false-positive rate is 0.5 %. The following screening policies were examined: NIPT or FTS with sum risk cut-offs of 1 in 50 and 1 in 250 in all patients or a two-step-policy with FTS in all patients followed by NIPT in the intermediate sum risk group. For the intermediate risk group, sum risk cut-offs of 1 in 50 and 1 in 1000 and 1 in 150 and 1 in 500 were used.Results: There were 127, 34, 13 and 15 pregnancies with trisomy 21, 18, 13 and sex chromosomal abnormalities. 23 fetuses had other chromosomal abnormalities with an increased risk for adverse outcome that are not detectable by NIPT. 20 840 pregnancies were classified as normal as ante- and postnatal examinations did not show any signs of clinically significant chromosomal abnormalities. FTS with a sum risk cut-off of 1 in 50 and 1 in 250 detects 81 % and 91 % for all aneuploidies. NIPT detects 88 % of the respective pregnancies. The 2-step approach with sum risk cut-offs of 1 in 50 and 1 in 1000 detects 94 % of all aneuploidies. With sum risk cut-offs of 1 in 150 and 1 in 500, the detection rate is 93 %.Conclusion: A 2-step policy with FTS for all patients and NIPT in the intermediate risk group results in the highest detection rate of all aneuploidies.
Keywords: first trimester; trisomy; nuchal translucency; NIPT